2019
DOI: 10.1038/s41598-018-37347-3
|View full text |Cite|
|
Sign up to set email alerts
|

Comparisons of different indices of low muscle mass in relationship with cardiometabolic disorder

Abstract: This study aimed to evaluate the most valid index among various indices of low muscle mass in assessing cardiometabolic risks in a Korean population. Appendicular lean mass index (ALMI, kg/m2), fat mass index (FMI, kg/m2), FMI-adjusted ALMI (ALMfmi), ratio of ALM to weight index (ALMwt), ratio of ALM to body mass index (ALMbmi) and ratio of ALM to truncal fat index (ALMtrunkfat) were measured by dual energy X-ray absorptiometry in 17,870 participants from 2008 to 2011. We adopted all the aforementioned indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Previous studies have shown that low muscle mass stands out in females. 46,47 Despite the same BMI, females have a lot of fat and low muscle mass mainly due to hormones and partially due to different exercise. In a previous study on the sex difference between skeletal muscle mass and prognosis in GC patients, skeletal muscle mass was an important prognostic factor in males, but not in females, 48 which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that low muscle mass stands out in females. 46,47 Despite the same BMI, females have a lot of fat and low muscle mass mainly due to hormones and partially due to different exercise. In a previous study on the sex difference between skeletal muscle mass and prognosis in GC patients, skeletal muscle mass was an important prognostic factor in males, but not in females, 48 which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers found low positive correlations between the two parameters in normal subjects. The subjects considered in our study belong to second and third quartiles of BMI that cover a broad range of weight, height and length of arm of normal and healthy human beings, excluding malnutrition and obese subjects 43 . We note that the reported range of ST (6.8–14.8 mm) in our work is well within the accepted norms of the second and third quartiles of BMI 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The anthropometric measures of the subjects recruited in this experiment cover broad ranges of the weight, height and LA of the global population comprising different races, as discussed by 42 . All the subjects belonged to second and third quartiles of BMI excluding malnutrition and obese subjects 43 . The study was approved by the local Medical Research & Ethics Committee (MREC), Ministry of Health, Malaysia (NMRR-14-822-22001) and adhered to the guidelines established by the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…High fat and low muscle mass in individuals with obesity adversely affect cardiometabolic risk factors, promoting hyperglycemia, hypertension, and dyslipidemia, among others [ 123 , 124 ]. Evaluating body composition, male rats that received L-Cit (1 g/kg/day) supplementation decreased fat mass and increased total body lean mass, which is mainly muscle, compared with control rats [ 117 ].…”
Section: Effects Of L-citrulline Supplementation On Vascular and Metabolic Parameters In Obesitymentioning
confidence: 99%